Edge‐Driven Convection Melting Before the Emplacement of the Afar Mantle Plume Head Inferred From 40Ar/39Ar Dating. Issue 8 (11th April 2023) - Yoshimura, Yutaka; Ishizuka, Osamu; Yamazaki, Toshitsugu; Ahn, Hyeon‐Seon; Kidane, Tesfaye; Yamamoto, Yuhji; Sekimoto, Shun; Sano, Takashi; Otofuji, Yo‐ichiro
Abstract: The Ethiopia‐Yemen flood basalts are spatially zoned with progressively lower TiO2 lavas from near the Afar depression toward the margins. The timing and rate of emplacement of low TiO2 (LT) lavas are poorly known compared with the ultra‐high TiO2 (HT2) lavas. We measured two high‐precision 40 Ar/ 39 Ar ages of 29.63 ± 0.14 and 30.02 ± 0.22 Ma (2σ) from basalts of the 2‐km‐thick LT lava sequence at the Afar plume head margin. Using our eruption age model constructed from our and previous 40 Ar/ 39 Ar ages with the paleomagnetic directions, we estimate that the LT lava eruption continued over Chrons C12r‐C12n‐C11r. The eruption of the plume head margin started earlier than the plume head axis emplacement in C12n. Also, the eruption rate was low at the margin, high at the axis. We estimate that the LT lavas are induced by the edge‐driven convection, the result of a plume‐lithosphere interaction, not a plume head. Plain Language Summary: The Ethiopia‐Yemen Flood Basalts are thought to be the expression of a mantle plume erupting millions of km 3 of basaltic lava in a geologically short period (1–3 million years [Myr]). Titanium concentrations in the flood basalts are zoned and named HT2, HT1, and LT basalts (from high to low Ti). The eruption timing and rate of the HT2 basalts are constrained with high precision, but those of the LT basalts remain ambiguous. Therefore, we measured two high‐precision 40 Ar/ 39 Ar ages from LT basalts in the 2‐km‐thick Lima‐Limo section, which erupted northwest of the Afar area. Based on our eruption age model constructed from 40 Ar/ 39 Ar ages and paleomagnetic directions, we estimate that the eruption of the LT basalts started earlier than the HT2 basalts that erupted in Chron C12n and lasted over at most ∼2 Myr. The eruptive rate of the LT basalts in the earliest interval was lower than that of the HT2 basalts. This feature of the eruption may be explained by edge‐driven convection caused by the interaction of a gradient of the lithospheric thickness with the Afar mantle plume. Key Points: We obtained two new 40 Ar/ 39 Ar ages for the low‐Ti basalt from the Lima‐Limo section of the Ethiopia–Yemen flood basalts Based on our eruptive age model, we correlated the Lima‐Limo section to Chrons C12r to C11r We concluded that the non‐plume low‐Ti basalts erupted before the Afar plume high‐Ti basalts because of the plume–lithosphere interaction